2001
DOI: 10.1002/cne.1185
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of the taste buds in the blind cave fish Astyanax jordani (“Anoptichthys”) and the sighted river fish Astyanax mexicanus (Teleostei, Characidae)

Abstract: This study describes the ultrastructure of the taste buds of the sighted river fish Astyanax mexicanus and of the blind cave fish Astyanax jordani (= Anoptichthys) (Teleostei, Characiformes, Characidae). In Astyanax and Anoptichthys, taste buds occur in the epithelia of the lips, oral cavity, and, in Anoptichthys, lower jaw. Both possess three types of taste buds: type I (elevated), type II (slightly elevated), and type III taste buds (not elevated or sunken). The taste buds are up to 60 microm high and up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…2A–D, G; Table 1). We also compared taste buds in embryos of the two forms of Astyanax because it has been reported that cavefish adults exhibit more taste buds than surface fish, particularly in the external surface of the lower jaw (Schemmel, 1967; Bensouilah and Denizot, 1991; Boudriot, and Reutter, 2001). Previous studies showed that Astyanax embryos begin to form calretinin-positive taste buds at 3–4 dpf (Jeffery et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2A–D, G; Table 1). We also compared taste buds in embryos of the two forms of Astyanax because it has been reported that cavefish adults exhibit more taste buds than surface fish, particularly in the external surface of the lower jaw (Schemmel, 1967; Bensouilah and Denizot, 1991; Boudriot, and Reutter, 2001). Previous studies showed that Astyanax embryos begin to form calretinin-positive taste buds at 3–4 dpf (Jeffery et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Taste buds are more numerous in adult cavefish than in surface fish (Schemmel, 1967; Boudriot, and Reutter, 2001 (Schemmel, 1980), and this expanded gustatory sense may be beneficial for cave life. Overexpression of shh has been previously detected in the ventral forebrain and Shh signaling domains in the developing cavefish brain (Menuet et al, 2006) but feeding structures have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…This may at least partly explain the low numbers of TB observed in symbiotic gobies dwelling in live corals, such as P. echinocephalus and Gobiodon spp., where they feed on a narrow and well‐recognized variety of food items found on the coral tissue. Such differences were also observed between some species of flatfishes (Livingston, 1987), between the holosteans Amia calva L. and Lepisosteus oculatus Winchell (Reutter et al ., 2000), and also recently described, although for a different reason, for Astyanax jordani (Hubbs & Innes) and Astyanax mexicanus (De Filippi)(Boudriot & Reutter, 2001), and between species of cardinal fishes (Fishelson et al ., 2004). …”
Section: Discussionmentioning
confidence: 99%
“…Based on electron‐density under transmission electron microscopy light and dark gustatory cells are distinguishable in fish TBs. Light and dark gustatory cells, which are supposed to be receptor cells (Reutter, ; Boudriot & Reutter, ), together with elongated supporting cells make up the bulk of the TBs (Figure ). In general, the apical microvillar structures of light and dark cells differ markedly from each other; light cells mostly terminate in one conical large villus, while the dark cells bear several small and sometimes divided microvilli.…”
Section: The Anatomy and Physiology Of The Taste System In Fishesmentioning
confidence: 99%